Reliability issues and improvement of preliminaries cost related items for civil engineering conventional contracts - Abdul Aziz Abas,; Faridah Ismail,; Zulhabri Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Civil engineering is a professional discipline that deals with built environment which involves physical construction of man-made structures such as roads, rails, bridges, drains, water supply, geotechnical systems, and services. It also deals with soft skills such as maintenance, research and investigation, conservation, and planning. In Malaysia, it is a prerogative that civil engineers administer civil engineering contracts. The preliminaries are an integral part of the bill of quantities and difficult to price due to their nature. However, the contractor is expected to price all items fully. The engineer prepares the preliminaries but the risk and liabilities are ultimately transferred to the contractor notwithstanding the reliability of the bill itself. As such, the reliability of preliminaries is of the utmost concern. The research focused on the improvement of the reliability of the preliminaries. The aim is to improve the effectiveness of present preliminaries in Civil Engineering conventional contracts. The objectives are, (1) To investigate the existing cost of item consideration and strategic approaches, (2) To improve the criteria of cost-related item components and expand their potential strategies. This paper considered previous research findings and highlighted the issues and problems related to the fallacy of the subject. Based on the preliminary survey (N=18), it was obvious that the issues concerning the reliability of preliminaries do exist. The research proceeded with a mass survey (N=270) of stratified data sampling involving Malaysian civil engineering contractors belonging to G7 CE21 class, as well as civil engineering consultants and developers. The survey used Likert scales, which ranged from 1 for “Strongly Disagree” to 5 for “Strongly Agree”. The analysis predominantly used SPSS statistics. The results conspicuously exposed the issues and the weaknesses of present practices. The improvement in the criteria of the present practices’ is expected to increase the reliability of preliminaries. As a way forward, the improved criteria provide better clarity, accuracy, and transparency to engineers and contractors as well as other construction players in general. Reliable preliminary items improve price accuracy for the betterment of the construction industry.